New empirical conversion technique for 1-minute integration time of precipitation intensity in Malaysia - Khairolanuar, Muhamad Haziq; Ismail, Ahmad Fadzil; Jusoh, Ahmad Zamani; Mohd Sobli, Nuurul Hudaa; Abdul Malek, Norun Farihah; Ahamad Zabidi, Suriza (AENSI Publications, 2014)
The suitability of previously proposed techniques claim to be able toaccurately convert precipitation intensity statistics at longer integration times into 1-minute integration time statistics has been of great interest to many wirelesspropagation researchers. Measured data of precipitation intensity collected in KualaLumpur, Malaysia had enabled the production of statistics at various integration timesof interest. Objective: An investigation has been embarked with the aim to devise anew empirical technique that capable to generate a more precise statistic at 1-minuteintegration time. Results: The study outlines the use of polynomial relationship in theprocess of converting statistics of longer integration time to 1-minute integration time.The generated 1-minute statistics using the new method were then compared with thoseof measured statistics in order to assess the technique‟s effectiveness. Conclusion: Itcan be suggested that the new conversion technique appears to be capable of producingconsistent statistics for 1-minute integration time from various other integration times.